Outer Membrane Protein OmpB Methylation May Mediate Bacterial Virulence. Issue 12 (December 2017) - Yang, David C.H.; Abeykoon, Amila H.; Choi, Bok-Eum; Ching, Wei-Mei; Chock, P. Boon
Abstract : Methylation of outer membrane proteins (OMPs) has been implicated in bacterial virulence. Lysine methylation in rickettsial OmpB is correlated with rickettsial virulence, and N- and O-methylations are also observed in virulence-relevant OMPs from several pathogenic bacteria that cause typhus, leptospirosis, tuberculosis, and anaplasmosis. We summarize recent findings on the structure of methylated OmpB, biochemical characterization, and crystal structures of OmpB methyltransferases. Native rickettsial OmpB purified from highly virulent strains contains multiple clusters of trimethyllysine, in contrast with mostly monomethyllysine, and no trimethyllysine is found in an avirulent strain. Crystal structure of the methyltransferases reveals mechanistic insights for catalysis, and a working model is discussed for this unusual post-translational modification. Trends: Protein methylation plays vital roles in cellular regulation and signaling. Bacterial chemotaxis is regulated by methylation of specific membrane proteins to mediate excitation and adaptation in response to chemotaxis. O-Methylation of Msp4, a surface protein, is required for Anaplasma phagocytophilum –mediated infection, and multisite N-methylation of OmpB correlates with typhus rickettsial virulence. Structural and mechanistic analysis of the newly characterized rickettsial methyltransferases led us to propose a mechanism in which the enzyme catalyzes multimethylation of OmpB. We believe that knowing the catalytic and regulatory mechanism of OMP methylation, and how methylated OMP exerts its virulent effect, would provide new insights to facilitate the development of novel therapeutic and diagnostic strategies.